2020
DOI: 10.1016/j.psj.2020.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with glycosaminoglycans reduces locomotor problems in broiler chickens

Abstract: This study aimed to assess the influence of glycosaminoglycan (chondroitin and glucosamine sulfates) supplementation in the diet on the performance and incidence of locomotor problems in broiler chickens. A completely randomized design was carried out in a 3 × 3 factorial scheme (3 levels of chondroitin sulfate −0, 0.05, and 0.10%; and 3 levels of glucosamine sulfate −0, 0.15, and 0.30%). Each treatment was composed of 6 replications of 30 broilers each. The performance of broilers (average weight, weight gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
3
6
0
Order By: Relevance
“…As observed, the sulfates increased calcium, phosphorus, and sodium ions and reduced chlorides in the chickens' blood, which suggests a possible action of these sulfates in reducing the incidence of tibial dyschondroplasia. This was previously reported in a study by Martins et al (2020b), who observed not only a reduction in the incidence of tibial dyschondroplasia, but also a decrease in femoral degeneration and valgus and varus angular defects in broilers fed diets supplemented with chondroitin and glucosamine sulfates. These effects consequently influenced performance, which may be in part due to the increased levels of these minerals in the blood.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As observed, the sulfates increased calcium, phosphorus, and sodium ions and reduced chlorides in the chickens' blood, which suggests a possible action of these sulfates in reducing the incidence of tibial dyschondroplasia. This was previously reported in a study by Martins et al (2020b), who observed not only a reduction in the incidence of tibial dyschondroplasia, but also a decrease in femoral degeneration and valgus and varus angular defects in broilers fed diets supplemented with chondroitin and glucosamine sulfates. These effects consequently influenced performance, which may be in part due to the increased levels of these minerals in the blood.…”
Section: Resultssupporting
confidence: 80%
“…The association of chondroitin and glucosamine sulfates has a proven effect on the bone and cartilaginous development of broilers (Santos et al, 2018(Santos et al, , 2019Sgavioli et al, 2017), consequently preventing locomotor problems (Martins et al, 2020b) and improving performance (Martins et al, 2020b;Martins et al, 2020a;Sgavioli et al, 2017). However, no studies have been done on the hematology and serum biochemistry of broilers fed diets containing GAGs.…”
Section: Amongmentioning
confidence: 99%
“…Polysulfated glycosaminoglycans, chondroitin and glucosamine, have been studied as nutraceuticals for the prevention and/or treatment of pathologies of bone and joint structures in broilers ( Sgavioli et al, 2017 ; Santos et al, 2018 , 2019 ; Martins et al, 2020a ), and consequently better performance ( Sgavioli et al, 2017 ; Martins et al, 2020a , b ). However, there is no research in broilers that has analyzed the inclusion of GAGs in the diet on the expression of genes related to the degradation of proteins in cartilage and the synthesis of proteoglycans and collagen type II.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, it can be paralleled with flattened distal tibiotarsal condyles and/or displacement of the gastrocnemius tendon. VV angulation can occur bilaterally or unilaterally ( Leterrier and Nys, 1992 ; Shim et al 2012 ; Guo et al, 2019 ) and valgus occurs more often than varus in broiler chickens ( Leterrier and Nys, 1992 ; Shim et al, 2012 ; González-Cerón et al, 2015 ; Martins et al, 2020 ). Incidence of VVD varies considerably among studies from 1.75% to 66.0% ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of VVD varies considerably among studies from 1.75% to 66.0% ( Table 1 ). Possible reasons for this huge variation in VVD incidence among studies might be related to differences in growth rate, body weight, genetics, housing system, lighting schedule, age, litter quality, and diet composition (see Bradshaw et al, 2002 for review; Almeida Paz et al, 2010 ; González-Cerón et al, 2015 ; Martins et al, 2020 ). However, another contributing factor that might explain the variation in reported incidence rates is the method used to determine VVD.…”
Section: Introductionmentioning
confidence: 99%